Dari Meja Layanan ke Dunia Profesional: Pembentukan Kesiapan Kerja melalui Interaksi Pelanggan dan Tim di PT. Kopi Mesra Abadi di Surabaya - Ferdiansyah Satya Adinata; Isa Anshori (YASIN, 2026)
Work readiness is an important aspect that the younger generation needs to possess before entering the workforce, especially in facing the dynamics of the service industry that demand technical skills and interpersonal abilities. Internship programs serve as one of the effective learning means in shaping work readiness through direct experience in a professional environment. This study aims to analyze the process of forming the work readiness of internship participants through interactions with customers and team-work dynamics at PT. Kopi Mesra Abadi Surabaya. This study employed a qualitative approach with a field research method. Data were collected through in-depth interviews with senior employees, participatory observation during operational activities, and documentation to strengthen the research findings. The analysis based on symbolic interactionism theory shows that work readiness is formed through a process of interpreting symbols and repeated social experiences. The results show that the internship program plays an important role in shaping participants’ work readiness through social interaction in the workplace. Internship participants not only learned technical skills in café service, but also developed interpersonal communication skills, teamwork, the ability to adapt to a dynamic work rhythm, and a professional attitude in serving customers. Guidance from senior employees and experience in interacting directly with customers became the main factors supporting this process. These findings confirm that the café service counter functions not only as a space for work practice, but also as a space for the formation of professional identity and work readiness that is adaptive to the demands of the working world. The implications of this study show the importance of integrating internship programs more systematically into higher education curricula, as well as providing a reflective and collaborative work environment to strengthen the formation of internship participants’ work readiness.